2016
DOI: 10.18203/2349-2902.isj20162716
|View full text |Cite
|
Sign up to set email alerts
|

A study of preoperative predictive factors of strangulation in acute small intestinal obstruction

Abstract: INTRODUCTIONAcute intestinal obstruction is a common surgical emergency with small bowel obstruction being the most common cause accounting for more than 80% of the cases. 1 Obstructed hernias had been the commonest cause for acute intestinal obstruction in the past. In the recent times with increase in the number of laparotomies performed for various reasons, post-operative adhesions has been the most common cause documented.The most critical factor affecting the outcome among these patients is whether obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(6 reference statements)
1
0
0
Order By: Relevance
“…Like our study, several previous publications found a significant correlation between II (and/or strangulation and/ or bowel resection) on the one hand, and pain duration before admission [5,15], body temperature [10,16], and WBC [1,5,[16][17][18] on the other hand.…”
Section: Distribution Of Intestinal Ischaemia According To Probabilit...supporting
confidence: 84%
“…Like our study, several previous publications found a significant correlation between II (and/or strangulation and/ or bowel resection) on the one hand, and pain duration before admission [5,15], body temperature [10,16], and WBC [1,5,[16][17][18] on the other hand.…”
Section: Distribution Of Intestinal Ischaemia According To Probabilit...supporting
confidence: 84%